PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA SMA KELAS XI DENGAN MENGGUNAKAN MODEL INKUIRI DI SMAN 4 CIMAHI - Kirana Nelis Amelia; Wikanengsih Wikanengsih; Yesi Maylani Kartiwi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is based on learning to write which is difficult for some students when writing explanatory text. The use of innovative learning models can certainly increase students' creativity and critical thinking skills independently with one of these learning models, namely the inquiry model. The purpose of this study was to find out how the students' abilities in learning to write explanatory text using the inquiry model. This study used a qualitative descriptive method with a research sample of 24 students of class XI MIPA. The results of research on learning to write explanatory text on the (pretest) initial action obtained an average of 53, and after being given action (posttest) using the inquiry learning model obtained an average of 76.16. Through the application of this inquiry model, it is proven to be effective in learning to write explanatory texts.